Modulation of Visual Cortical Excitability by Working Memory: Effect of Luminance Contrast of Mental Imagery - Cattaneo, Zaira; Pisoni, Alberto; Papagno, Costanza; Silvanto, Juha (Frontiers in Psychology, 2011)
Although much is known about the impact of stimulus properties such as luminance contrast, spatial frequency and orientation on visually evoked neural activity, much less is known about how they modulate neural activity when they are properties of a mental image held in working memory (WM). Here we addressed this question by investigating how a parametric manipulation of an imagined stimulus attribute affects neuronal excitability in the early visual cortex. We manipulated luminance contrast, a stimulus property known to strongly affect the magnitude of neuronal responses in early visual areas. Luminance contrast modulated neuronal excitability, as assessed by the frequency of phosphenes induced by transcranial magnetic stimulation (TMS) with the exact nature of this modulation depending on TMS intensity. These results point to a strong overlap in the neuronal processes underlying visual perception and mental imagery: not only does WM maintenance selectively engage neurons which are tuned to the maintained attribute (as has previously been shown), but the extent to which those neurons are activated depends on the luminance contrast (as is the case with visually-evoked responses). From a methodological viewpoint, these results suggest that assessment of visual cortical excitability using TMS is affected by the TMS intensity used to probe the neuronal population.